Relationships between university students’ achievement motivation, attitude and academic performance in Malaysia - Abu Bakar, Kamariah; Ahmad Tarmizi, Rohani; Mahyuddin, Rahil; Elias, Habibah; Wong, Su Luan; Mohd Ayub, Ahmad Fauzi (Elsevier, 2010)
Student achievement problems are often highlighted in academic literature and the mass media and therefore, it is pertinent for educators to be aware and to study the factors related to student achievements such as achievement motivation and attitude. The purpose of this study was to identify the relationships between the achievement motivation, attitude and student academic performance. The research design employed was a descriptive correlational. Data were collected by self-reported questionnaire on a sample using cluster sampling technique based on the different faculty of studies in the university. The respondents were 1484 students from a local university (1102 females and 382 males). They were following the education, science, humanities, agriculture/technical/engineering programmes. Results indicated a positive significant correlation between students’ attitude towards learning and achievement motivation (r= 0.53, p < .001), and between students’ attitude and academic achievement (r = 0.16, p < .001). However, a negative and low correlation (r=-.038, p > .05) was observed between students’ achievement motivation (nAch) and their academic achievement. The implications of the findings were also discussed in the paper.